Harorepupu aotearoa (Onygenales) gen. sp. nov.; a threatened fungus from shells of Powelliphanta and Paryphanta snails (Rhytididae) - Johnston, Peter R; Nguyen, Hai D T; Park, Duckchul; Hirooka, Yuuri (Université d'Ottawa | University of Ottawa, 2015)
Abstract A cleistothecial fungus, known only from the shells of giant land snails of the family Rhytidae, is described as a new genus and species within Onygenales, Harorepupu aotearoa gen. sp. nov. Known only from the sexual morph, this fungus is characterized morphologically by a membranous ascoma with no appendages and ascospores with a sparse network of ridges. Ribosomal DNA sequences place the new species within Onygenales, but comparison with the known genetic diversity within the order linked it to no existing genus or family. It is the first species of Onygenales reported from the shells of terrestrial snails. This fungus has been listed as Critically Endangered in New Zealand and has been previously referred to as ‘Trichocomaceae gen. nov’ in those threat lists.